Wittgenstein and religious dogma - Hoyt, Christopher (International journal for philosophy of religion, 2007)
It is well understood that Wittgenstein defends religious faith against positivistic criticisms on the grounds of its logical independence. But exactly how are we to understand the nature of that independence? Most scholars take Wittgenstein to equate language-games with belief-systems, and thus to assert that religions are logical schemes founded on their own basic beliefs and principles of inference. By contrast, I argue that on Wittgenstein’s view, to have religious faith is to hold fast to a certain picture of the world according to which one orients one’s actions and attitudes, possibly even in dogmatic defiance of contrary evidence. Commitment to such a picture is grounded in passion, not intellection, and systematic coherence is largely irrelevant.